Hama Orygtes di Perkebunan Kelapa Sawit - Dwika Sadewa; Arif Solahuddin Dalimunthe; Parhan Fauzan Rambe; M. Iswan; M. Ilham Pasaribu; Yegi Ardana; M. Reynaldi Hidayat (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
This study uses a qualitative method to describe the infestation of Oryctes rhinoceros beetles in oil palm plantations and its impact on crop productivity. This pest poses a major threat to oil palm cultivation due to its ability to damage the growing points of both young and mature plants, resulting in a significant decline in yield. The study was conducted through field observations and in-depth interviews with farmers and field technicians at an oil palm plantation in Sumatra. The findings reveal that Oryctes infestations are more prevalent in plantations with poor sanitation and limited implementation of regular biological control systems. Farmers predominantly rely on mechanical and chemical control methods, which have proven to be less effective due to the lack of coordinated and sustainable application. Therefore, an ecologically-based integrated pest management strategy is needed, combining biological control, cultural practices, and farmer education to effectively suppress pest populations and ensure the sustainability of oil palm production.